Hacı Ibrahim Efendi (1242/1826-1307/1889) and His Private School for Teaching Arabic : "Daru't-Ta'lim" - Arslan, Ahmet Turan (Sheikh Zayed Islamic Centre University of Karachi, 1999)
[No Abstract Available]